2014
DOI: 10.3389/fpls.2014.00235
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic auxin transport patterns preceding vein formation revealed by live-imaging of Arabidopsis leaf primordia

Abstract: Self-regulatory patterning mechanisms capable of generating biologically meaningful, yet unpredictable cellular patterns offer unique opportunities for obtaining mathematical descriptions of underlying patterning systems properties. The networks of higher-order veins in leaf primordia constitute such a self-regulatory system. During the formation of higher-order veins, vascular precursors are selected from a homogenous field of subepidermal cells in unpredictable positions to eventually connect in complex cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 41 publications
10
49
0
Order By: Relevance
“…Vascular tissues differentiate in regions where auxin concentration is elevated (Aloni 2001), and the localization of the intensive auxin flow in the developing leaf reflects the future vascular strand placement (Scarpella et al 2006; Wenzel et al 2007; Marcos and Berleth 2014). Moreover, exogenous application of auxin or its transport inhibitors drastically changes venation patterning (Sieburth 1999; Mattsson et al 1999, 2003; Scarpella et al 2006).…”
Section: The Role Of Auxin Transport In Leaf Vascularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular tissues differentiate in regions where auxin concentration is elevated (Aloni 2001), and the localization of the intensive auxin flow in the developing leaf reflects the future vascular strand placement (Scarpella et al 2006; Wenzel et al 2007; Marcos and Berleth 2014). Moreover, exogenous application of auxin or its transport inhibitors drastically changes venation patterning (Sieburth 1999; Mattsson et al 1999, 2003; Scarpella et al 2006).…”
Section: The Role Of Auxin Transport In Leaf Vascularizationmentioning
confidence: 99%
“…The theory of canalization has been confirmed in many mathematical models (Mitchison et al 1981; Rolland-Lagan and Prusinkiewicz 2005; Merks et al 2007; Bayer et al 2009; Lee et al 2014) as well as in experimental studies (Mattsson et al 1999, 2003; Sauer et al 2006; Scarpella et al 2006; Wenzel et al 2007). Main support for this theory comes from the characterization of the mechanism driving canalized polar auxin flow (Scarpella et al 2006; Wenzel et al 2007; Marcos and Berleth 2014) and the identification of some of its molecular components (Vieten et al 2007). …”
Section: The Role Of Auxin Transport In Leaf Vascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, live imaging revealed that cells in PIN1 expression domains differentiate into vascular and nonvascular cells in leaf primordia (Marcos and Berleth, 2014). These nonvascular cells subsequently downregulate PIN1 expression and maintain ground meristem cell morphology (isodiametric shape) (Marcos and Berleth, 2014).…”
Section: Relationship Between Myrosin Cell Development and Vascular Cmentioning
confidence: 99%
“…These nonvascular cells subsequently downregulate PIN1 expression and maintain ground meristem cell morphology (isodiametric shape) (Marcos and Berleth, 2014). These ground meristem cells might subsequently differentiate into myrosin cells.…”
Section: Relationship Between Myrosin Cell Development and Vascular Cmentioning
confidence: 99%